2011
DOI: 10.1029/2010jd014234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stratospheric water vapor enhancements caused by CH4and H2O increase on polar ozone loss

Abstract: [1] Possible causes of a future increase in stratospheric H 2 O are increasing tropospheric methane levels and a rise in tropospheric H 2 due to leakages from a possible increased integration of hydrogen into the energy supply system. Here we quantify the direct chemical impact of potential future stratospheric H 2 O increases on Arctic ozone loss using the cold Arctic winter 2004/2005 as the basis for our study. We present simulations with the three-dimensional chemistry transport model CLaMS using enhanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 53 publications
(146 reference statements)
2
49
1
Order By: Relevance
“…6b. This is in contrast to the findings of Kirk-Davidoff et al (1999), Feck (2008) and Vogel et al (2011), who found that cooler temperatures resulting from increases in water vapour lead to enhanced heterogeneous chlorine chemistry and subsequent ozone loss. It is likely that because we focus on the 2090s decade in our analysis, when stratospheric chlorine levels are very low, heterogeneous chemistry is no longer of significance to polar ozone depletion.…”
Section: Ozone Changes Resulting From Chemistrycontrasting
confidence: 55%
“…6b. This is in contrast to the findings of Kirk-Davidoff et al (1999), Feck (2008) and Vogel et al (2011), who found that cooler temperatures resulting from increases in water vapour lead to enhanced heterogeneous chlorine chemistry and subsequent ozone loss. It is likely that because we focus on the 2090s decade in our analysis, when stratospheric chlorine levels are very low, heterogeneous chemistry is no longer of significance to polar ozone depletion.…”
Section: Ozone Changes Resulting From Chemistrycontrasting
confidence: 55%
“…70 The chemical ozone destruction over the Arctic in early 2011 was, for the first time in the observational record, comparable to that in the Antarctic ozone hole with a maximum accumulated ozone loss of up to approximately 130 DU. 71 In a study recently published by Vogel et al 57 (2011) using the 3-dimensional chemistry transport model CLaMS, 72- 57 For both scenarios S2 and S4, the calculated ozone loss is much smaller than the existing variability of ozone loss observed in cold Arctic winters. 70 It should be noted that simulations focusing on the stratospheric impact of additional hydrogen economy differ from each other not only in the model or method used, but also in the assumptions related to chemical or physical processes.…”
Section: Impact On Ozone-climate Interactionsmentioning
confidence: 99%
“…4,6,57 Because the H 2 leakage rate deduced by Tromp et al 3 (2003) was assessed to be unrealistically high, 1,2,4,6,47 the impact of a potential hydrogen economy on the stratospheric ozone loss is obviously overestimated. The findings of other studies 4,6,56,57,67 vary somewhat as a result of using different models and techniques. However, all these studies suggest that a future potential hydrogen economy would have a minor impact on Arctic ozone loss.…”
Section: Impact On Ozone-climate Interactionsmentioning
confidence: 99%
See 2 more Smart Citations